Strategi Ketahanan Ekonomi Guru PAUD melalui Kewirausahaan - Evi Octrianty; Susan Maulani; Revita Yanuarsari; Dianti Yunia Sari; Siti Rodiah Basyar (LPPI UMN AL WASHLIYAH, 2025)
The low income of PAUD teachers is currently caused by the provision of teacher salaries which are only funded by the school, because they are only appointed by the principal. The obligations and workload of PAUD teachers which are almost the same as ASN teachers are not commensurate with the income and spirit of dedication carried out with the salary they receive, even what is received is smaller than the salary of a laborer. This condition makes PAUD teachers continue to struggle to get a decent income and hope to achieve good welfare. This study aims to: 1) find out the strategies of PAUD teachers, especially in Bandung Regency, in carrying out their roles as entrepreneurs, 2) find out the activities of PAUD teachers in facing economic resilience through their business paths, and 3) find out the obstacles faced by PAUD teachers when undergoing entrepreneurship, and its impact on PAUD teacher income. This study uses a qualitative approach with a naturalistic qualitative descriptive method. The data sources consist of 7 respondents of PAUD teachers who are entrepreneurs from 3 PAUD institutions that are members of the Small Micro Medium Enterprises (UMKM community) in Bandung Regency. The results of the study show that PAUD teachers who are entrepreneurs have better economic resilience, but there are obstacles found, namely equipment and marketing that are still lacking in support, so it is necessary to develop business strategies through digital marketing and other special strategies so that the business continues to increase.